Some properties of particleboard panels treated with extractives of Cerbera odollam tree - Razak Wahab; Rokiah Hashim; Mohd Hazim Mohd Amini; Othman Sulaiman (Sage, 2011)
This study investigated certain aspects of physical and mechanical properties and resistance against biological deterioration of particleboard panels treated with extractives from different parts of Cerbera odollam trees. Particles of rubber-wood (Hevea brasiliensis) treated with extracts of leaf, fruit, wood, bark, flower, and seed of Cerbera odollam were used to manufacture panels in laboratory conditions. Two types of adhesive, namely melamine urea formaldehyde and phenol resorcinol formaldehyde were used as binder for the panels. Treated panels had higher resistance against powder post beetle in laboratory as well as field exposures. Both thickness swelling and internal bond strength values of treated samples satisfied requirements for P4 Type particleboards stated in European Standards (EN 312). It appears that such extractives possess potential to enhance resistance of particleboard against insect damage in tropical countries.